Intractable Epilepsy in Children - GHOFRANI, Mohammad; AKHONDIAN, Javad (Iranian Journal of Child Neurology, 2010)
Objective Epilepsy is a common disorder affecting approximately 1% of the population. It is estimated that about 20- 30% of the patients become refractory to proper medical therapies. Such cases are often termed intractable. Intractable epilepsy (IE) is a serious condition in children, leading to significant impairment in quality of life, as well as behavioral and psychiatric problems. In this review, we tried to define intractability, mention the causes of intractable epilepsy and its predictive factors in children, and outline the management and various treatments of intractable epilepsy.